Features and Limitations of Mobile Tablet Devices for Viewing Radiological Images - Grunert, J. H. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2015)
Purpose: Mobile radiological image display systems are becoming increasingly common, necessitating a comparison of the features of these systems, specifically the operating system employed, connection to stationary PACS, data security and rang of image display and image analysis functions.Material and methods: In the fall of 2013, a total of 17 PACS suppliers were surveyed regarding the technical features of 18 mobile radiological image display systems using a standardized questionnaire. The study also examined to what extent the technical specifications of the mobile image display systems satisfy the provisions of the Germany Medical Devices Act as well as the provisions of the German X-ray ordinance (RöV).Results: There are clear differences in terms of how the mobile systems connected to the stationary PACS. Web-based solutions allow the mobile image display systems to function independently of their operating systems. The examined systems differed very little in terms of image display and image analysis functions.Conclusion: Mobile image display systems complement stationary PACS and can be used to view images. The impacts of the new quality assurance guidelines (QS-RL) as well as the upcoming new standard DIN 6868 – 157 on the acceptance testing of mobile image display units for the purpose of image evaluation are discussed.Key Points:• The examined mobile image display systems differ very little in terms of image display and analysis functions.• The use of web-based software allows the mobile image display systems to function independently of their operating systems.• Individual PACS suppliers enable the mobile systems to connect to the network via their own internet server.• With zero-footprint technology, no patient data remains on the viewing system once the application is closed.Citation Format:• Grunert JH. Eigenschaften und Einschränkungen mobiler radiologischer Bildwiedergabesysteme. Fortschr Röntgenstr 2015; 187: 173 – 179
Keywords: PACS; image manipulation/reconstruction; QA/QC; technical aspects; mobile viewing; tablet PC